Rewriting the Damsel’s Fate: A Deconstructive Feminist Analysis of Damsel (2024) Movie and the Subversion of Fairy Tale Narratives - Djohan, Febrina Stevani; Surya, Michaella Isabel; Nathanael, Jeshua; Sihombing, Cleary Arnold; Kawulusan, King David Lie (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2026)
This research examines the movie Damsel (2024) through the lens of Jacques Derrida’s narrative deconstruction (2016). The issue shown in the movie is patriarchal expectations that portray women as a passive figure and as a sacrificial. The purpose of this study is to examine how Damsel challenges the traditional fairy tale trope by showing a female protagonist who reclaims her agency through survival and resistance. This study used a qualitative method while examining scenes and narratives. The result shows that: 1) Damsel deconstructs traditional fairy tale narratives by positioning the princess as her own savior; 2) The movie subverts patriarchal expectations by resisting the rigid tradition of female sacrifice; and 3) Elodie’s survival is portrayed as an act of resistance against societal control. The conclusion of the study highlights that Damsel offers a feminist reinterpretation of the traditional fairy tale trope. The significance of this research is the contribution to feminist movies, demonstrating how modern literature or movies can redefine women’s role in narratives. It is hoped that future researchers will further explore other fairy tales that challenge traditional gender roles similar to Damsel (2024).